The Influence of Challenge Leadership, Gratitude and Happiness As Intervening Variables on Employees at PT PNM Banyuwangi Branch - Subekti, Aries; Prasadjaningsih, MC. Oetami (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
In an increasingly competitive organizational environment, employee commitment is essential for sustaining performance and achieving strategic goals. This study investigates the influence of challenge leadership and gratitude on employee commitment, with happiness as an intervening variable, among employees of PT. Permodalan Nasional Madani (PNM) Banyuwangi Branch. Employing a quantitative research design, data were collected through questionnaires distributed to 138 purposively sampled respondents and analyzed using Structural Equation Modeling with SmartPLS 3.0. The study tested seven hypotheses involving direct and mediated relationships between the constructs. The results showed that challenge leadership has a significant direct and indirect (via happiness) impact on employee commitment, while gratitude significantly influences happiness but does not directly or indirectly affect employee commitment. Furthermore, happiness was not found to have a significant effect on employee commitment. The model demonstrated strong validity and reliability, with satisfactory fit indices. This study contributes to the literature by integrating emotional and leadership dimensions in the Indonesian context and emphasizing the conditional role of happiness as a non-linear or context-specific mediator. The findings suggest that to enhance employee commitment, organizations should prioritize leadership approaches that challenge and empower employees while fostering gratitude to improve workplace happiness. Future research is encouraged to explore moderating variables such as organizational culture or job autonomy and examine alternative mediators like psychological capital in broader industrial contexts.